2018
DOI: 10.1257/aer.20160613
|View full text |Cite
|
Sign up to set email alerts
|

Equal but Inequitable: Who Benefits from Gender-Neutral Tenure Clock Stopping Policies?

Abstract: Many skilled professional occupations are characterized by an early period of intensive skill accumulation and career establishment. Examples include law firm associates, surgical residents, and untenured faculty at research-intensive universities. High female exit rates are sometimes blamed on the inability of new mothers to survive the sustained negative productivity shock associated with childbearing and early childrearing in these environments. Gender-neutral family policies have been adopted in some profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
243
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(252 citation statements)
references
References 46 publications
4
243
3
2
Order By: Relevance
“…Liberal feminism is the predominant view for campuses striving to improve the conditions of the workplace for women and is the basis for creating most workplace family‐friendly policy. Our research and that of others (e.g, Sallee, ; Antecol et al., ), however, shows that adding more women or creating more policies is not enough to generate equal career outcomes for men and women. A liberal view helps identify gender inequality, but it fails to dig into nuanced understandings of equity and gender.…”
Section: Theoretical Perspectivescontrasting
confidence: 71%
See 1 more Smart Citation
“…Liberal feminism is the predominant view for campuses striving to improve the conditions of the workplace for women and is the basis for creating most workplace family‐friendly policy. Our research and that of others (e.g, Sallee, ; Antecol et al., ), however, shows that adding more women or creating more policies is not enough to generate equal career outcomes for men and women. A liberal view helps identify gender inequality, but it fails to dig into nuanced understandings of equity and gender.…”
Section: Theoretical Perspectivescontrasting
confidence: 71%
“…A few “truths” are evident from looking at the research related to work, family, and the academic career: (a) tenure‐track academic careers are “greedy” and call for total commitment to faculty life, and ideal workers are rewarded (Hochschild, ); (b) parenting, and more directly mothering, is demanding, and being a “good” mother calls for an intensive, and preferably exclusive, commitment to the mother role (O'Brien Hallstein & O'Reilly, ); (c) women have greater access to the academic workplace than they have had historically, but access has not converted to advancement and equity; and, (d) many colleges and universities have created and updated work–family policies (e.g., parental leave and tenure‐clock stop policies), yet these policies tend to be underutilized for fear of bias (Ward & Wolf‐Wendel, ) and have not had desired outcomes (Antecol, Bedard, & Stearns, ).…”
Section: Related Literaturementioning
confidence: 99%
“…An analysis of data on all assistant professors hired at top-50 economics departments from 1985 to 2004 found that gender-neutral policies to stop the tenure clock for new parents substantially reduce female tenure rates while substantially increasing male tenure rates (Antecol, Bedard, and Stearns 2016). As another example, desire to have women and minority representation on committees may help explain why women faculty are asked to provide more service, as a survey of 1,399 members of US political science departments found (Mitchell and Hesli 2013).…”
mentioning
confidence: 99%
“…Antecol et al (2016) show that gender-neutral policies that provide extra time (often one year) in cases of ill-health or childbirth aimed at dealing with this disadvantage, faced mostly by women, appear ineffective at helping women (but do help men in obtaining tenure). This may be due to the fact that eligibility for the relevant policy does not require taking time off or showing that a substantial amount of time is spent in caring for children.…”
Section: The Dynamics Of Labour Supplymentioning
confidence: 99%